Career Aspirations of Slovenian Ninth Graders: The Influence of Personal Factors and Attitudes Towards Engineering Professions - Ploj Virtič, Mateja; Košak, Igor; Šorgo, Andrej (Revija za elementarno izobraževanje, 2025)
The study examines the career aspirations of Slovenian ninth-grade students and analyses how these are influenced by personal factors and their attitudes towards engineering professions. Regression analyses on a sample of 779 students show that interest in outdoor work is a significant predictor of engineering career aspirations across all educational levels. Physical demands positively influence aspirations for engineering occupations requiring secondary or elementary education, while intellectual demands and employment opportunities encourage interest in engineering occupations at the tertiary level. A positive perception of engineering professions as interesting is a key factor for all levels of education. The results emphasise the importance of fostering interest in technical careers.
Keywords: ninth grade students, career aspirations, engineering professions, personal factors influencing career choice, attitudes towards engineering professions.